Keynote: Being transformed – presence and partipation - Juncker, Beth (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2016)
Professor Beth Juncker has criticized the DICE Report to exaggerate its conclusions. At the same time, she notes that in relation to the Nordic countries there has not been done much to develop creative, innovative and communicative skills. The challenge is that in the drama and theater sphere educational responses are still being sought to legitimate and integrate the value-in-itself-ness that characterizes paradigms in aesthetic and artistic learning-processes. Professor Beth Juncker will seek to answer vitally: How can working with art and culture lead to a paradigm, which in its practice form with drama and theater has the ‘Now’ and ‘Presence’ as a driving force?